Clinical findings and electrocardiography predicted mortality among COVID-19 patients with pre-existing hypertension: A cross-sectional study of East Java Province, Indonesia - Makhyan Jibril Al Farabi; Pandit Bagus Tri Saputra; Amanda Marantika; Diar Pasahan; Runn Rami; Yudi Her Oktaviono (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the factors associated with mortality among coronavirus disease-2019 patients with preexisting hypertension. Method: The retrospective, cross-sectional study was conducted from June 15 to July 7, 2021, after approval from Dr Soetomo General Province Hospital, Indonesia, and comprised data from the coronavirus disease-2019 registry in the East Java province of Indonesia from March 2020 to June 2021. Data was collected for adult patients infected by coronavirus disease-2019 with pre-existing hypertension Data was analysed using SPSS 23. Results: Of the 2,732 patients in the registry, 425(15.6%) with median age 56.5 years (interquartile range: 50-64 years) had pre-existing hypertension. Of them, 251(59.06%) were males, and 110(25.9%) had died while in hospital. Mortality was associated with older age; higher white blood cell counts at admission and lower platelet count (p<0.05). In addition, electrocardiogram parameters associated with mortality were faster heart rate and ST abnormality (p<0.05). Conclusion: Older age, high white blood cell level, lower platelet count, faster heart rate, and ST abnormality at admission were found to be the predictors of mortality among hospitalised coronavirus disease-2019 patients with pre-existing hypertension. Key Words: COVID-19, Hypertension, Electrocardiography, Leukocytes.